Transtornos convulsivos associados a oligodendroglioma cão boxer - Relato de caso - Torres, Alexandre Arenales [UNESP]; Galvão, André Luiz Baptista [UNESP]; De Oliveira Vasconcelos, Rosemeri [UNESP] (My University, 2013)
At necropsy examination of the central nervous system of a Boxer dog, female, 8 years old, with not pharmacological control of seizures, was detected a focal area in white matter in the middle region of the right piriform lobe, approximately 2 cm diameter, expansive and well defined. Cut surface with reddish and gelatinous appearance. In microscopy we observe a high cell density in white matter, with cells arranged in sheets similar to normal oligodendrocytes. The cytoplasm showed up a large, perinuclear halo, with a small, central, round, dark staining nucleus and hyperchromatic chromatin. We visualized a low nuclear atypia and no mitotic figures, but intense vascularization of the tumor, with formations of vessels with thickened walls, irregularly distributed throughout proliferation, and large cysts filled with amorphous granular eosinophilic material. The diagnosis being compatible with oligodendroglioma.
Seizure disorders associated oligodendroglioma in boxer dog - Case report
Keywords: Brachycephalic; Oligodendroglioma; Seizures